Intake of fruit and leaves of sweet cherry beneficially affects lipid metabolism, oxidative stress and inflammation in Wistar rats fed with high fat-cholesterol diet. (June 2019) - Dziadek, Kinga; Kopeć, Aneta; Piątkowska, Ewa
Graphical abstract: Highlights: Fruit and leaves of sweet cherry can be used for the development of functional foods. Sweet cherry, especially leaves, improved the lipid profile and liver function. Fruit and leaves caused changes in gene expression involved in lipid metabolism. Fruit and leaves reduced oxidative stress and inflammation. Abstract: The aim of this study was to assess the effect of an addition of sweet cherry fruit or leaves (unexplored until now) to high fat-cholesterol (HFC) diet on selected biochemical parameters and expression of genes involved in fatty acid metabolism in male Wistar rats. The addition of sweet cherry fruit and leaves to HFC diet resulted in decrease in body gain, improvement of the liver function as well as reduction of oxidative stress and inflammation. Additionally, fruit and leaves had a beneficial impact on lipid metabolism, thereby reducing lipid accumulation in liver and improving lipid profile in the serum. These effects result from the regulation of expression of fatty acid synthesis and oxidation-related genes. It can be summarized that not only fruit of sweet cherry but also leaves, may have a potential application in the fight against non-communicable diseases, especially obesity and cardiovascular diseases.